Framing the Gen Z protesters in Kenyan daily newspapers: A discourse-historical approach - Karambu, Joy; Ngumo, Mugambi C; Omoke, Lillian (Research Journal in Advanced Humanities, 2026)
This study examines how Kenya’s mainstream newspapers, The Daily Nation and The Standard, discursively constructed Gen Z protesters during the June 24 anti-Finance Bill demonstrations. Existing studies of Gen Z protests in Kenya and globally overwhelmingly focus on digital media. Relatively little attention has been given to how newspapers frame such political movements. To address this gap, this study analyses front-page headlines and editorials in the newspapers to explore how Gen Z are constructed. Drawing on Ruth Wodak’s Discourse-Historical Approach and Framing Theory, the findings reveal a systematic pattern of positive representation, in which Gen Z protesters are constructed as heroic, victorious, revolutionary, victims of police brutality, and morally legitimate actors. Their actions are intensified when aligned with democratic ideals, while negative aspects are mitigated through nominalization, backgrounding, and silence. This framing is reinforced through intertextual references to Gen Z protests in other parts of the world. The interdiscursivity in the editorials further gives the protesters legal justification. Recontexualization of constitutional language in journalistic discourse, particularly the constant reference to articles 1 and 37, legitimizes the actions of the protesters. This study demonstrates the ideological role of newspapers in influencing the way we think about politics and youth activism. These findings are aligned with the observations of media scholars that newspapers are an important site for studying politics and ideology.